PAYROLL ADMINISTRATION SYSTEM PT. PAKARTI USING VISUAL BASIC 6.0 - Mintarsih Mintarsih; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2005)
The author chose this title "Payroll Administration System PT. PAKARTI using Visual Basic 6.0. "Because it follows the era that has developed rapidly, especially in computerization. In making the new system required the old system. In this paper the author wants to explain changes in the old system to new, more perfect system. With the new system is expected programming errors can be reduced. So that at the moment do not have problems processing the data and the information obtained is always in a state accurately. Making the report can be done precisely and quickly so that computer use can be more efficient and effective.